Aspectos fisiológicos de grãos de café, processados e secados de diferentes métodos, associados à qualidade sensorial - Oliveira, Pedro Damasceno [UNESP]; Borém, Flávio Meira; Isquierdo, Eder Pedroza; Giomo, Gerson da Silva; de Lima, Renato Ribeiro; Cardoso, Renan Alves (My University, 2013)
The objective of the present study was to evaluate the physiological and sensory quality of coffee beans processed and dried in different manners. The experiment was conducted with two types of processing - dry and wet processing, and four drying methods - drying in a drying yard, and mechanical drying with heated air at three alternating temperatures (50/40°C, 60/40°C and 40/60°C) where the temperature was changed when the coffee beans reached moisture content of 30% ± 2% (w.b.), with supplementation of drying until achieveing 11% ± 1% (w.b.). The mechanical drying system used consisted of three fixed bed dryers, which allows control of temperature and flow drying rate. After application of the treatments, the coffees were sampled according to the evaluation system proposed by the Specialty Coffee Association of America (SCAA). In addition to sensory analysis, analyses were made of the physical-chemical and physiological quality of the coffee beans. The physical-chemical and physiological analyses involved: fatty acid composition, leaching of potassium, electrical conductivity and germination. Interesting results were obtained. Coffee dried in the drying yard showed better sensory, physiological and physical-chemical results when compared with that dried in a dryer. Pulped coffee was more tolerant to drying than natural coffee, regardless of the way it was dried, showing better final quality of the product. Moreover, it may be observed that the increase in drying temperature in the final phase of the drying process leads to grain damage, which notably reduces beverage quality, confirming existing research.
Physiological aspects of coffee beans, processed and dried through different methods, associated with sensory quality
Keywords: Beverage analysis; Physiological quality; Post-harvest